Silencing of the chemokine CXC receptor 4 (CXCR4) hampers cancer progression and increases cisplatin (DDP)-sensitivity in clear cell renal cell carcinoma (ccRCC). Issue 1 (1st January 2021) - Wang, Wenguang; Gan, Zhilu; Liu, Qiang; Yan, Shenshen; Mulati, Rexiti; Wang, Yujie
ABSTRACT: Aberrant expression of the chemokine CXC receptor 4 (CXCR4) is closely associated with cancer progression and drug-resistance in multiple cancers, and we first investigated the role of CXCR4 in regulating cancer pathogenesis and cisplatin (DDP)-resistance in clear cell renal cell carcinoma (ccRCC) in the present study. Here, we identified that CXCR4 acted as an oncogene to promote cancer progression and genetically silencing of CXCR4 increased cisplatin (DDP)-sensitivity in ccRCC in vitro and in vivo . Functionally, analysis from the clinical and cellular data indicated that CXCR4 was significantly upregulated in ccRCC tissues and cells, compared to their normal counterparts. Next, the loss-of-function experiments validated that knock-down of CXCR4 suppressed cell proliferation, invasion, migration and epithelial-mesenchymal transition (EMT) in ccRCC cells, while CXCR4 overexpression had opposite effects on the above cellular functions. Consistently, the xenograft tumor-bearing mice models were established, and the results supported that knock-down of CXCR4 inhibited tumor growth and the expression levels of Ki67 protein in vivo . In addition, the ccRCC cells were exposed to DDP treatment, and we surprisingly found that upregulation of CXCR4 increased DDP-resistance in ccRCC cells, and conversely, CXCR4 ablation sensitized ccRCC cells to DDP stimulation. Taken together, we concluded that CXCR4 ablation hindered cancer progression and enhanced DDP-sensitivity in ccRCC, and the present study identified a novel therapeutic biomarker for ccRCC. GRAPHICAL ABSTRACT: uf0001